Rhizobium leguminosarum hupE Encodes a Nickel Transporter Required for Hydrogenase Activity - Brito, Belén (American Society for Microbiology (ASM), 2010)
Synthesis of the hydrogen uptake (Hup) system in Rhizobium leguminosarum bv. viciae requires the function of an 18-gene cluster (hupSLCDEFGHIJK-hypABFCDEX). Among them, the hupE gene encodes a protein showing six transmembrane domains for which a potential role as a nickel permease has been proposed. In this paper, we further characterize the nickel transport capacity of HupE and that of the translated product of hupE2, a hydrogenase-unlinked gene identified in the R. leguminosarum genome. HupE2 is a potential membrane protein that shows 48% amino acid sequence identity with HupE. Expression of both genes in the Escherichia coli nikABCDE mutant strain HYD723 restored hydrogenase activity and nickel transport. However, nickel transport assays revealed that HupE and HupE2 displayed different levels of nickel uptake. Site-directed mutagenesis of histidine residues in HupE revealed two motifs (HX(5)DH and FHGX[AV]HGXE) that are required for HupE functionality. An R. leguminosarum double mutant, SPF22A (hupE hupE2), exhibited reduced levels of hydrogenase activity in free-living cells, and this phenotype was complemented by nickel supplementation. Low levels of symbiotic hydrogenase activity were also observed in SPF22A bacteroid cells from lentil (Lens culinaris L.) root nodules but not in pea (Pisum sativum L.) bacteroids. Moreover, heterologous expression of the R. leguminosarum hup system in bacteroid cells of Rhizobium tropici and Mesorhizobium loti displayed reduced levels of hydrogen uptake in the absence of hupE. These data support the role of R. leguminosarum HupE as a nickel permease required for hydrogen uptake under both free-living and symbiotic conditions.